Prevalensi dan Analisis Faktor Risiko Multidrug Resistance Bakteri Escherichia coli pada Ayam Komersial di Kabupaten Blitar - Wibisono, Freshinta Jellia; Sumiarto, Bambang; Untari, Tri; Effendi, Mustofa Helmi; Permatasari, Dian Ayu; Witaningrum, Adiana Mutamsari (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2020)
Multidrug resistance is a problem that is difficult to overcome in terms of treating infectious diseases. Multidrug resistance is the term used to describe when a bacteria is resistant to three or more different classes of antibiotics. Escherichia coli as a commensal bacterium which has multidrug resistance, this causes more issues because Escherichia coli can transfer its resistant properties to other bacteria within the poultry digestive tract. The observational study is used to determine the risk factors and to estimate the quantitative effects arising from various components that contribute to the emergence of a disease. The sampling in this study was carried out randomly through cloaca swabs from commercial chicken farms in Blitar and 345 samples were collected. Complementary data collection was carried out using questionnaires, interviews, and field observations. The results showed the incidence of multidrug resistance in commercial chickens in the Blitar District was 72.5%. There is a relationship between causative factors with the incidence of multidrug resistance in Escherichia coli bacteria that is significantly associated with positive risk factors. The strength of this relationship can be seen from the value of OR and RR, among others factors of chicken breed (OR = 3.07; RR = 1.34), breeder's education (OR = 2.3; RR = 1.29), type of livestock business (OR = 7.5; RR = 1.43), type of animal feed (OR = 1.91; RR = 1.2), veterinary support for livestock raising management (OR = 3.09; RR = 1.44). The reference variables are whether the antibiotics are administered by non-veterinarians (OR = 2.35) or by the TS (OR = 7.92), and whether there is an antibiotic administration program (OR = 3.16; RR = 1.47). The overseeing function of farm maintenance, management, and implementation of antimicrobial administration in commercial chicken farms needs to be improved, to increase breeders' awareness of the careful usage of antibiotics and controlling the incidence of antibiotic resistance.